Education philosophies - the key to understanding the role of teacher's beliefs in education practice - Kunac, Sani (Array, 2020)
The contemporary paradigm in pedagogy is focused on a holistic development of an individual through a curricular approach, accentuating the results of learning and teaching. The important and active role of a student in class is emphasized, but also the importance of teacher’s role as the person who shapes the learning environment and who organizes the teaching process. The teacher’s educational philosophy and their beliefs in the background have a great impact on their teaching practice and their actions during class. But there are still discrepancies in definition, identification and classification of educational philosophies. The aim of this paper is to provide an overview of the educational philosophy literature, to contribute to the construct definition, to point out the importance of educational philosophy research within pedagogy and to point out the connection between the teacher's educational philosophy and the different aspects of their educational impact.